Ekstraksi DNA dari Daging Segar untuk Analisis dengan Metode Loop-Mediated Isothermal Amplification (LAMP) - Rosy Hutami; Hanifah Bisyri; Sukarno Sukarno; Henny Nuraini; Raafqi Ranasasmita (Universitas Djuanda, 2018)
DNA extraction is needed in the analysis using the Loop-mediated isothermal amplification (LAMP) method because this method identifies nucleic acids. Some extraction methods that can be selected including commercial kits extraction method and phenol-chloroform extraction method. The purpose of this study was to obtain the best quality DNA extract between the two extraction methods. The DNA extraction process produced DNA concentrations between 31.06 - 410.18 ng / ml for the commercial kit DNA extract and 212.60 - 1502.30 ng / ml for the phenol-choroform DNA extract, while the purity of DNA were 1.82-2.02 for commercial kit DNA extract and 1.93-2.02 for phenol-chloroform DNA extract. The concentration and purity of extracts produced from both methods meet the requirements for molecular analysis. The purity and visualization results of commercial kit DNA extract are better than those produced from extraction from the phenol-chloroform method. DNA extract obtained from the commercial kit method was chosen to be used in the amplification stage of the method (LAMP).